다문화 가정 아동의 언어에 관한 문헌연구 - 박세희(Se Hee Park); 황보명(Bo Myung Hwang) (언어치료연구, 2015)
목적: 본 연구는 사회적 논점인 다문화 가정 아동들의 언어에 대한 국내 연구를 분석하여 그 동향을 밝히고 앞으로 연구의 방향성을 제시하고자 하였다. 방법: 2000년부터 2015년까지 국내 학술지에 발표된 다문화 가정 아동의 언어에 대한 95편의 논문을 선정하여 연구현황, 연구 대상 분석, 연구 방법 분석, 연구 내용에 따라 분석하였다. 결과: 2008년 이후 연구가 본격적으로 이루어져 꾸준히 이루어지고 있었다. 특히, 유아기 아동을 대상으로 하는 논문이 35편 (39.8%)으로 가장 많이 연구되었고, 학령기 아동을 대상으로 한 연구논문은 21편 (23.9%) 이었다. 다문화 가정 아동의 언어능력을 평가하기 위하여 사용한 검사도구를 분석한 결과, 취학전 아동의 수용언어 및 표현언어 발달척도(PRES)를 22편 (16.2%)의 논문에서 사용하였으며, 지능검사로는 웩슬러 유아용지능검사(K-WPPSI)를 17편 (12.5%)의 논문에서 사용하였다. 연구 방법에 대한 분석에서는 조사연구가 69편 (72.6%)으로 가장 큰 비중을 차지하고 있으며, 다음으로 중재연구가 12편(12.6%)이었다. 종속변인으로 살펴 본 연구 내용 분석에서는 언어발달능력을 알아본 논문이 32편 (33.7%)으로 가장 많은 부분을 차지하고 있었다. 결론: 다문화 가정 아동을 대상으로 하여 다양한 영역과 연령대에서 연구가 이루어지고 있었다. 하지만, 학령기 아동 중 고학년 아동을 대상으로 하는 연구가 미약함을 알 수 있었다. 후속 연구에서는 학령기 아동들에 대한 언어발달과 관련된 특성을 지속적으로 연구할 수 있어야 할 것이다. 또한 다양한 연령의 아동들에 대한 중재연구가 필요함을 알 수 있었다. Purpose: Considering the steady growth of the number of studies related to multicultural families (MCF), it is important to determine the tendency of contemporary studies about language development of children from these families. The purpose of this study was to analyze studies that had investigated MCF children’s language, to understand study trends, and to suggest a future direction. Methods: A total of 95 research papers from national academic journals from 2000 to 2015 were selected. These papers focused on the language development of MCF children and were analyzed according to study status, subjects, research methods, and dependent variables. Results: Studies regarding the language development of MCF children had steadily been increasing since 2008. Thirty-five papers (39.8%) for infants and 21 papers (23.9%) for school-age children had been published in terms of research subject. Twenty-two papers (16.2%) used PRES as a language competence test and 17 papers (12.5%) utilized K-WIPPSI as an intelligence test. In terms of other research methods, 69 papers (72.2%) were research studies -- which was the most frequent research methodology -- while 12 papers (12.6%) were intervention studies. On the dependent variables as research content analysis, 72 papers (33.7%), the highest number, investigated the language development of the children. Conclusion: This study found that there were insufficient studies about children in the upper grades, while many studies in various language areas and ages had been conducted. Based on this study, a future direction regarding children with multicultural backgrounds is that the language characteristics of school-age children need to be further investigated. KCI Citation Count: 11